Violence and memory in the Peruvian narrative about the internal armed conflict - de Vivanco, Lucero (2024)
From the first years of the armed conflict between the Communist Party of Peru Sendero Luminoso (PCP-SL) and the Peruvian State, literature burst onto the cultural and social scene with the aim of interpreting its immediate situation and thus contributing to the production of meaning to understand that historical experience, both in the representation of violence and in the construction of memory. This essay proposes a global and complex look at this phenomenon, cultural and political at the same time, to identify and map out —from a limited corpus of novels— relevant thematic axes and their respective modes of representation.